The Effect of Competition Phase Loads on Anaerobic Efforts in Algerian Football Players - guerione, khaled (sports creativity, 2025)
According to Dufour (1989), 24% of the effort is within the anaerobic system (80% of VO2max) and 14% is running short distances for 2 seconds, which represents the anaerobic alactic system. Perhaps the most important thing indicating the importance of anaerobic metabolism in the technical and tactical performance in modern football is the increase in the number of short runs (10 to 15 meters) during matches lasting 2 to 3 seconds, from 70 times in 1947 to 140 times in 1970, then to 185 times in 1985, separated by rest periods estimated at at least 1 minute to allow for the ability to perform other anaerobic alactic efforts. This has led some researchers to emphasize the importance of sprinting in football, considering football to be an explosive sport (Cristian, 2001). As for Lacour and Chatard (1984), they believe that playing football requires sprinting separated by periods at speeds largely corresponding to aerobic metabolism. These demands help trigger anaerobic lactic metabolism, leading to a lactate accumulation in the blood at a level of 9 mmol/L, measured in several professional matches. Based on these studies, most of the Technical-tactical tasks performed during competition with maximum and near-maximum intensity, such as running, jumping, and changing direction with or without the ball to try to deceive the opponent, led us to seek to understand the effect and extent of the effect of the competition phase loads on anaerobic efforts.